Development of a Self-defense Model for Women in the Sport of Karate Dojo - Marco Van Johan Manalu; Indra Kasih; Albadi Sinulingga (Randwick International of Social Science Journal, 2023)
The purpose of this study was to develop self-defense methods for women in the Karate Dojo Inkanas Tebing Tinggi branch. This research is a type of research and development or Research and Development (R&D). The design used in this study is the development research of Borg and Gall. The subjects of this study consisted of 10 people for small group trials and 30 people for large group trials. In the first (small) group trial, research results were obtained with 10 test subjects from the dojo of SMA Brigjend Katamso Medan and the dojo of SMKN 6 Medan, then a score of 85 was obtained with a percentage of 85% in a small trial (valid). Based on the results of expert validation, it was obtained that from Power Ginting as a karate expert obtained a score of 8 with a percentage of 80% (valid/feasible). Then the assessment from Pangondian Purba as an expert in sports movement skills obtained a score of 8 with a percentage of 80% (valid/feasible). So on a small trial scale, the product of the self-defense method module for women in karate is valid. In the second (large) group trial, research results were obtained with 30 test subjects from the dojo of SMA Negeri 1 Tebing Tinggi, then a score of 272 was obtained with a percentage of 90.66% in the large trial valid). Based on the results of expert validation, it was obtained that from Power Ginting as a karate expert obtained a score of 9 with a percentage of 90% (valid/feasible). Then the assessment from Pangondian Purba as an expert in sports movement skills obtained a score of 9 with a percentage of 90% (valid/feasible). So on a large trial scale the product module self-defense methods for women in karate sports is valid. In this expert revision, there are no more revisions made by experts, so the product of the self-defense method module for women in rubber sports is feasible.